Engaging community organizations for undergraduate medical education curriculum renewal - Muldoon, Laura; Chenier, Annick; Campbell, Craig; Kendall, Claire E (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2023)
Implication StatementAs part of its social accountability mission, the University of Ottawa Faculty of Medicine invited community service learning (CSL) partner organizations to a guided, virtual conversation on April 12, 2021 to contribute to the future strategic directions for our curriculum. Representatives of 15 organizations participated and provided insights into how they perceive CSL students, the Faculty of Medicine, and the process of assessment. This workshop forged stronger bonds between the university and these community organizations and led to recommendations for their greater involvement going forward, an approach that could be considered by other Faculties of Medicine.